AFRICA AND GLOBALIZATION: RETHINKING THE MORAL PRINCIPLES OF COSMOPOLITANISM IN THE LIGHT OF CATHOLIC SOCIAL TEACHING - Nwachukwu-Udaku, Benedict C (Asian Horizons, 2011)
The notion of globalization is no longer an imaginary concept. The last few decades of the inevitable interaction among people of different geographical locations and economic potentialities provide positive data demonstrating that globalization is a reality in nearly every local community. Everybody talks about it, but many are unaware of the devastating consequences it has on people who are vulnerable to different social and economic problems. Globalization is a phenomenon that has strong economic, political, social, religious and cultural dimensions, and has indisputably produced a twofold dialectic.1 The one is a dialectic of differentiation whereby we are made increasingly aware of our cultural identity. This seemingly negative dialectic unveils why we are different from other people with respect to our nationality, culture, religion, ethnicity, gender, class, language etc. The other is a dialectic of interdependence whereby we become more aware of our need for others irrespective of any natural or conventional difference that may define our relationship with them. The later is positively oriented, hence it constitutes a bridge that brings people together to bring about an enduring cosmopolitanism.